Pharmacological Activities of Sonneratia Alba Mangrove Plant : A Review - Rizki, Andita Fitri Mutiara; Azmi, Wihda Aisarul; Muhaimin, Muhaimin; Louisa, Melva; Artika, I Made; Siregar, Josephine Elizabeth (Journal of The Indonesian Society of Integrated Chemistry, 2023)
Indonesia is a country with a high amount of diverse natural resources. Various plants have important roles in supporting human medicinal needs due to their availability in providing various medicinal resources. One of the natural resources is Sonneratia alba, a species of mangrove plant known with high adaptive ability and tolerance to extreme environmental conditions such as high saline stress, light intensity exposure, and free radicals. This review summarized the findings on pharmacological activities of S. alba.Â  Several studies reported the adaptive ability of S. alba with its various pharmacological activities such as antimalarial, antioxidant, antimicrobial, and anticancer. These activities are strongly correlated with its bioactive constituents such as terpenoid, alkaloid, tannin, quinone, phenolic, and flavonoid. The mechanism of each pharmacological activity has been suggested in several studies. These findings could be beneficial in drug discovery for several infectious and degenerative diseases and in the development of drugs at industrial stage. Keyword: Anticancer, antimalaria, antimicrobial, antioxidant, Sonneratia alba Â